2021
DOI: 10.3389/fchem.2021.661143
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Responsive Supramolecular Drug Delivery System Constructed by Cationic Pillar[5]arene for Enhancing Antitumor Activity

Abstract: Drug delivery systems have good biocompatibiliy and low side effects for cancer treatment, but overcoming high efficiency of drug-loading and the drug-targeting controlled release still remains challenging. In this work, supramolecular vesicles, with pH-triggering effect, have been successfully constructed for drug delivery, which are fabricated by the complexation between a cationic pillar[5]arene (DAWP5) and a sodium dodecyl sulfonate (SDS) in aqueous solution. Drug-loading and releasing results demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
(41 reference statements)
2
17
0
Order By: Relevance
“…13 Liu et al designed supramolecular nanovesicles based on cationic pillar [5]arenes (PR5) with pH-responsive effect for targeted delivery of doxorubicin (DOX). 14 The cationic PR5, composed of D-alanine functionalized water-soluble PR5, was formulated into nanovesicles encapsulating DOX via the host− guest inclusion complexation with sodium dodecyl sulfonate (SDS) in a ratio 1:3 followed by self-assembly in an aqueous medium. The designed spherical nanovesicles loaded with DOX had a size of 220 nm, a zeta potential of 30.8 mV, and an encapsulation efficiency of 75%.…”
Section: Pillar[n]arenes (Prs)mentioning
confidence: 99%
See 2 more Smart Citations
“…13 Liu et al designed supramolecular nanovesicles based on cationic pillar [5]arenes (PR5) with pH-responsive effect for targeted delivery of doxorubicin (DOX). 14 The cationic PR5, composed of D-alanine functionalized water-soluble PR5, was formulated into nanovesicles encapsulating DOX via the host− guest inclusion complexation with sodium dodecyl sulfonate (SDS) in a ratio 1:3 followed by self-assembly in an aqueous medium. The designed spherical nanovesicles loaded with DOX had a size of 220 nm, a zeta potential of 30.8 mV, and an encapsulation efficiency of 75%.…”
Section: Pillar[n]arenes (Prs)mentioning
confidence: 99%
“…Furthermore, the DOX loaded cationic PR5 nanovesicles exhibited significant cytotoxicity (IC50 values of 0.77 μM and 1.09 μM against HepG2 and T24 cancer cell lines, respectively) compared to free DOX (IC50 values of 3.43 μM and 1.76 μM against HepG2 and T24 cancer cell lines, respectively) (Figure 2). 14 Guo et al designed a hydrazide-pillar [5]arene (HPA5)/ bisdemethoxycurcumin (BDMC) host−guest inclusion complex with 1:1 binding stoichiometry and association constant of 1.6 × 10 4 ± 0.3 M −1 . 15 This complex was further selfassembled in water/ethanol solution to form supramolecular nanofibers.…”
Section: Pillar[n]arenes (Prs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pillararenes (P­[ n ]­A) are promiscuous molecules due to their versatile functionalization and ability to be used as hosts for several kinds and sizes of guest molecules by enlarging their cavities. For biological applications, a variety of biocompatible pillararenes have been proposed by the judicious choice of functional groups. In recent years, P­[ n ]­A have been widely explored as a component of drug delivery systems, e.g., vesicles, micelles, nanoparticles, and nanogates for switchable devices. , Previously, we demonstrated that cationic ammonium pillar[5]­arene can be used as a nanogate by interacting with spherical anionic MS nanoparticle surfaces, indicating that cationic-substituted pillar[5]­arenes are promising switchable components for blocking silica pores . To the best of our knowledge, N -methylimidazolium-pillar­[5]­arene (MIP5 + ) has not been explored as a cationic nanogate for MSNs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transformation between membranes and vesicles is a significant phenomenon, the lack of a detailed understanding of the transformation at the molecular level can limit the development of synthetic systems to mimic the natural and reversible dynamic system. Therefore, investigations via synthetic model systems in the detailed mechanisms of such sophisticated membrane transformations can provide a tool for emerging synthetic materials, such as those required for drug delivery systems, , biosensors, and catalysts. …”
mentioning
confidence: 99%